Professional C++ - Gregoire, Marc (Indianapolis : John Wiley and Sons, 2020)
"This new fifth-edition of Professional C++ provides a code-intensitive, solutions-oriented guide to everything C++ has to offer, including the newest tools and features in the latest release. Packed with practical instructions geared toward real-world programming, this bok is the programmer's ideal opportunity to dig deeper into C++. The fifth edition covers C++20. Professional C++; Demonstrates how to think in C++ to maximize the language's far-reaching capabilities and develop effecive solutions. Explain poorly understood elements, warns against pitfalls, and shares tips, tricks, and workaround for efficiency and performance. Presents a variety of challenging, real-world program segments versatile enough to plug into any object. Highlights the new features of C++20 including modules, concepts, three-way comparisons, immediate functions, and much more. Features in-depth discussions of new C++20 Standard Library features, such as text formatting, ranges, atomic smart pointers, synchronization primitives, dates, time zones and more." -- Book cover
Keywords: C++ (Computer program language)